Mapping residual organics and carbonate at grain boundaries and the amorphous interphase in mouse incisor enamel - Gordon, Lyle M.; Joester, Derk (Frontiers in Physiology, 2015)
Dental enamel has evolved to resist the most grueling conditions of mechanical stress, fatigue, and wear. Adding insult to injury, it is exposed to the frequently corrosive environment of the oral cavity. While its hierarchical structure is unrivaled in its mechanical resilience, heterogeneity in the distribution of magnesium ions and the presence of Mg-substituted amorphous calcium phosphate (Mg-ACP) as an intergranular phase have recently been shown to increase the susceptibility of mouse enamel to acid attack. Herein we investigate the distribution of two important constituents of enamel, residual organic matter and inorganic carbonate. We find that organics, carbonate, and possibly water show distinct distribution patterns in the mouse enamel crystallites, at simple grain boundaries, and in the amorphous interphase at multiple grain boundaries. This has implications for the resistance to acid corrosion, mechanical properties, and the mechanism by which enamel crystals grow during amelogenesis.